Enhancing professional curriculum practice in a Grade 9 economic and management sciences class - Moloi, Mojakgomo David (University of the Free State, 2018)
This study aimed to design a strategy to enhance professional curriculum practice (PCP) for a Grade 9 economic and management sciences class (EMS) at a school in Thabo Mofutsanyana district. For this study to reach its aim, specific objectives were used to guide the study, namely, • To demonstrate and justify a need for strategies to enhance PCP in a Grade 9 EMS class; • To identify components to enhance PCP in a Grade 9 EMS class; • To anticipate possible risks and ways to mitigate and manage risk to enhance PCP in a Grade 9 EMS class; • To explore conditions conducive to the successful implementation of strategies to enhance PCP in a Grade 9 EMS class; and • To monitor the functionality of the strategy to improve PCP in a Grade 9 EMS class. This study is strengthened by critical pedagogy as theoretical framework. Critical pedagogy is an appropriate approach, because it emphasises that teaching and learning must marginalise the issue of power by liberating the oppressed and giving voices to the voiceless in order to promote social change. Critical pedagogy places the researcher and participants on the same level, with the intent of identifying challenges and designing a strategy and achieve the objectives of the study. I am in a position to understand the points of view of participants, that is, the views of Department of Education officials, teachers, principal and head of department who participated in this study. One school, Tlotlo School in Thabo Mofutsanyana, was used to generate data. Literature was reviewed on issues of PCP of EMS (accounting, economics and accounting) for the purpose of generating realistic data. Data confirms that there are multiple challenges facing PCP at schools in several countries globally, on the African continent, in the SADC and in South Africa, in relation to problems identified for the subject of EMS. Challenges identified by this study are insufficient subject content knowledge on the topic of cash journals, and ineffective collaboration in teaching the component subjects (accounting, economics and business studies) of EMS. Participatory action learning and action research (PALAR) methodology was adopted for this study to collect data, since PALAR equalises the value of the collaboration of the researcher and participants to identify the need for research, to decide on the best course of action, implement the action, evaluate it and then decide what further action to take, based on participants’ critical reflection on the process. PALAR is well- matched with critical pedagogy, as both approaches promote classroom liberation and emancipation in a respectful manner. In conclusion, the study argues that effective PCP cannot be achieved individually, but only through co-operative and collaborative teaching. The study trusts that the strategy that it proposes to enhance PCP of EMS in Grade 9 at a school in Thabo Mofutsanyana district, is effective. By achieving this, the study can contribute to the existing body of knowledge in literature about enhancing PCP in South Africa.
Dissertation (M.Ed. (Curriculum Studies))--University of the Free State, 2018
Keywords: Professional curriculum practice; Economic and management sciences (EMS); Grade 9